ANALISIS PENERIMAAN OPENAI CHATGPT OLEH MAHASISWA SURABAYA MENGGUNAKAN MODEL UTAUT 2 - Farrel Ega Nur Royyan; Adriano Femaz Rivaldy; Wahyu Setiawan (Jurnal Teknologi Informasi dan Komputer, 2025)
This study uses the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model to investigate and analyze the factors that may influence Surabaya university students in accepting and using ChatGPT. Data collection was conducted by conducting a questionnaire survey of 119 student respondents was used to collect data and Partial Least Squares - Structural Equation Modeling (PLS-SEM) was used to process the data. The findings show that the most important predictors of intention and behavior of using ChatGPT are habit and conducive circumstances. On the other hand, behavioral intentions were not significantly influenced by other factors including hedonic motivation, social influence, or performance expectations. These results suggest that ChatGPT adoption patterns have changed from initial impressions of ease of use or technological advantages to being based on routine and infrastructure support.